U937 cell apoptosis induced by arsenite is prevented by low concentrations of mitochondrial ascorbic acid with hardly any effect mediated by the cytosolic fraction of the vitamin. (23rd March 2015) - Guidarelli, Andrea; Fiorani, Mara; Azzolini, Catia; Cerioni, Liana; Scotti, Maddalena; Cantoni, Orazio
Summary Arsenite directly triggers cytochrome c and Smac/DIABLO release in mitochondria isolated from U937 cells. These effects were not observed in mitochondria pre‐exposed for 15 min to 10 µM L‐ascorbic acid (AA). In other experiments, intact cells treated for 24–72 h with arsenite were found to die by apoptosis through a mechanism involving mitochondrial permeability transition. Pre‐exposure (15 min) to low micromolar concentrations of AA and dehydroascorbic acid (DHA), resulting in identical cytosolic levels of the vitamin, had a diverse impact on cell survival, as cytoprotection was only observed after treatment with AA. Also the mitochondrial accumulation of the vitamin was restricted to AA exposure. An additional indication linking cytoprotection to the mitochondrial fraction of the vitamin was obtained in experiments measuring susceptibility to arsenite in parallel with loss of mitochondrial and cytosolic AA at different times after vitamin exposure. Finally, we took advantage of our recent findings that DHA potently inhibits AA transport to demonstrate that DHA abolishes all the protective effects of AA, under the same conditions in which the mitochondrial accumulation of the vitamin is prevented without affecting the overall cellular accumulation of the vitamin. © 2015 BioFactors, 41(2):101–110, 2015